2019
DOI: 10.30772/qjes.v12i3.612
|View full text |Cite
|
Sign up to set email alerts
|

Double-Diffusive of Natural Convection in an Inclined Porous Square Domain Generalized Model

Abstract: Numerical investigate of double-diffusive natural convection in an inclined porous square. Two opposing walls of the square cavity are adiabatic; while the other walls are, kept at constant concentrations and temperatures. The Darcy–Forchheimer–Brinkman model is used to solve the governing equations with the Boussinesq approximation. A code written in FORTRAN language developed to solve the governing equations in dimensionless forms using a finite volume approach with a SIMPLER algorithm. The results presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The authors found that at Ɵ = -45° and Ra =100, the average Nusselt number is the lowest value. Al-Farhany and Turan [19] studied the natural convection in an inclined enclosure. Adiabatic conditions were assumed for the top and bottom walls.…”
Section: Heat Transfer Inside Cavity With Porous Mediamentioning
confidence: 99%
“…The authors found that at Ɵ = -45° and Ra =100, the average Nusselt number is the lowest value. Al-Farhany and Turan [19] studied the natural convection in an inclined enclosure. Adiabatic conditions were assumed for the top and bottom walls.…”
Section: Heat Transfer Inside Cavity With Porous Mediamentioning
confidence: 99%